ANALISIS BEBAN KERJA PEGAWAI DIKANTOR URUSAN AGAMA KECAMATAN KUBU KABUPATEN ROKAN HILIR - Puja Lestari; Mimin Sundari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at the Office of Religious Affairs, Kubu District, Rokan Hilir Regency. The problem of this research is that there are many tasks and functions carried out by the employees of the religious affairs office in the Kubu Subdistrict, Rokan Hilir Regency, while the number of employees is very minimal, and there is a lack of public understanding of service requests such as marriage services, services. waqf, and also the implementation of cross-sectoral activities. The purpose of this study was to determine the analysis of workload and factors that hinder the workload of employees at the Office of Religious Affairs, Kubu District, Rokan Hilir Regency. In this study, researchers used a qualitative descriptive research method. In this study, researchers used observation and interview techniques. The theoretical concept used in this study was the Workload Analysis by Moekijat (2008). Which starts from calculating work time, time to complete tasks, and employee needs. The results of this study lead to the conclusion that the employees of the Office of Religious Affairs in Kubu District, Rokan Hilir Regency have a total workload of 1,530 hours per year. This total is above the productive time for civil servants, which is 1,200 hours per year. So it can be concluded that the amount of workload and the availability of labor for the Office of Religious Affairs employees is not balanced. Judging from the indicators, there are several factors that hinder the workload of employees in the religious affairs office in the downstream Kubu sub-district, Rokan Regency, namely: lack of budget, lack of staff, and lack of skills. Keywords: Workload Analysis, Religious Affairs Office Staff